Handbook of applied health economics in vaccines - Bishai, David; Brenzel, Logan; Padula, William (New York Oxford University Press, 2022)
Fundamentals matter. Vaccines are some of the most complex molecules ever invented and, the social systems that deploy, monitor, and finance them are equally complex. Much of the peculiarities of vaccine economics arises from the peculiarities of vaccines. The most eccentric thing about vaccines is that many of them can benefit the person who gets the shot as well as the people around them. Furthermore, not everyone will obtain the same amount of benefit because of varying risk levels in the population. COVID-19 vaccines illustrate these points well. The massive public investments to subsidize supply and stimulate demand of COVID-19 vaccines were predicated on a sure forecast that without public investment the free market was doomed to fail. In many countries, even with the public sector investments, a COVID-19 vaccine at a price of $0 was not attractive to many who were at lower risk and did not appreciate the benefits their shot would offer their community"--
Contents - - 1. Principles of vaccines economics / edited by David Bishai and Chrispus Mayora - - 1.0 Section introduction: principles of vaccine economics / David Bishai and Chrispus Mayora - - 1.1 Introdcution to global vaccine systems / Gatien de Broucker - - 1.2 Relevance of health economics to vaccines / David Bishai and Chrispus Mayora - - 1.3 Cost of finding and making vaccines: implications for immunization programs / Clarke B. Cole, Beth Evans, and Soleine Scotney - - 1.4. Vaccinations as investment in human capital / J.P. Sevilla, David Bloom, Dan Salmon, and David Bishai - - 1.5 Economics of vaccine delivery / George Pariyo and Onaopemipo Abiodun - - 2. Estimating the cost of immunization services / edited by Logan Brenzel - - 2.0 Section introduction: estimating the cost of immunization services / Logan Brenzel - - 2.1 Why costing studies are needed / Ann Levin, Stephen Resch, and Logan Brenzel - - 2.2 Defining immunization costs / Logan Brenzel - - 2.3 Designing a primary costing study or analysis / Ijeoma Edoka, Stephen Resch, and Logan Brenzel - - 2.4 Data analysis / Stephen Resch and Logan Brenzel - - 2.5 Costing new vaccine introduction / Susmita Chatterjee, Siriporn Pooripussarakul, and Logan Brenzel - - 3. Economic evaluation of vaccines and vaccine programs / edited by William V. Padula, Emmanuel F. Drabo, and Ijeoma Edoka - - 3.0 Section introduction: economic evaluation of vaccines and vaccine programs / William V. Padula, Emmanuel F. Drabo, and Ijeoma Edoka - - 3.1 Overview of decision analysis and cost-effectiveness / Emmanuel F. Drabo, Ijeoma Edoka, and William V. Padula - - 3.2 Defining the scope and study design of cost-effectiveness analysis / Joseph F. Levy and Charles E. Phelps - - 3.3 Parameter estimation / Emmanuel F. Drabo and David W. Dowdy - - 3.4 Measuring and valuing health outcomes / Y. Natalia Alfonso, Stephane Verguet, and Ankur Pandya -- 3.5 Reporting and interpreting results of economic evaluation / Ijeoma Edoka, Carleigh Krubiner, Andrew Mirelman, R. Brett McQueen, Mark Sculpher, Julia F. Slejko, and Tommy Wilkinson - - 3.6 Budget impact analysis and return on investment / Elizabeth Watts - - 3.7 Introduction to decision tree modeling / William V. Padula - - 4. Advanced methods in economic evaluation / edited by William V. Padula, Emmanuel F. Drabo, and Ijeoma Edoka - - 4.0 Section introduction: advanced methods in economic evaluation / Emmanuel F. Drabo and william V. Padula - - 4.1 Introduction to Markov modeling / Emmanuel F. Drabo and William V. Padula - - 4.2 Static and dynamic modeling / Ann Levin and Colleen Burgess - - 4.3 Probabilistic sensitivity analysis and value of information analysis / Ciara N. Kohli-Lynch - - 4.4 Economic evaluation reference case with Markov model information analysis / William V. Padula, Shreena Malaviya, Natalie M. Reid, Jonothan Tierce, and G. Caleb Alexander - - 5. Financing and resource tracking of vaccination programs / edited by Logan Brenzel and Shreena Malaviya - - 5.0 Section introduction: financing and resource tracking of vaccination programs / Logan Brenzel and Shreena Malaviya - - 5.2. Financing of immunization programs / Logan Brenzel - - 5.3 Donor architecture for immunization financing / Grace Chee, George Pariyo, and Shreena Malaviya.
Keywords: Vaccines -- Economic aspects; Medical economics